Modeling of the Water Uptake Process for Cowpea Seeds (Vigna Unguiculata L.) under Common Treatment and Microwave Treatment - Demirhan, Elcin; Ozbek, Belma (CHEM SOC PAKISTAN, 2015)
The water uptake kinetics of cowpea seeds were carried out at two different water absorption treatments - common treatment and microwave treatment - to evaluate the effects of rehydration temperatures and microwave output powers on rehydration. Water uptake of cowpea seeds during soaking in water was studied at various temperatures of 20 - 45 degrees C, and at various microwave output powers of 180 - 900 W. As the rehydration temperature and microwave output power increased, the water uptake of cowpea seeds increased and the rehydration time decreased. The Peleg's and Richards' Models were capable of predicting water uptake of cowpea seeds undergoing common treatment and microwave treatment, respectively. The effective diffusivity values were evaluated by fitting experimental absorption data to Fick's second law of diffusion. The effective diffusivity coefficients for cowpea seeds varied from 7.75x10(-11) to 1.99x10(-10) m(2)/s and from 2.23x10(-9) to 9.78x10(-9) m(2)/s for common treatment and microwave treatment, respectively.
Keywords: Cowpea; Water uptake; Physical properties; Effective diffusivity; Modeling; PHYSICAL-PROPERTIES; REHYDRATION CHARACTERISTICS; HYDRATION KINETICS; PELEGS EQUATION; MOISTURE UPTAKE; ABSORPTION; VARIETIES; SOAKING; PRETREATMENT; CHICKPEA; Chemistry